(untitled) (Texas Journal of Medical Science, 2023)
The aim of the research is to identify the reality of sports and scouting activities at the Directorate of Sports and Scouting Activity from the point of view of teachers and supervisors of physical education in Al-Qadisiyah Governorate. The research community was determined by teachers and supervisors of physical education in Al-Qadisiyah Governorate, whose number is (384) teachers and supervisors of physical education, and the research sample was chosen randomly and in a proportional distribution method, as the number of the research sample reached (192) teachers and supervisors, with (160) teachers and (32) supervisors From the total research community. With regard to sports activities, two fields were identified (sports races and refresher courses). As for scouting activities, two fields were identified (scout assemblies and training lessons). always - often - sometimes - rarely - never). An exploratory experiment was conducted to identify the most important obstacles that the researcher may face in the future, then the main experiment (the building experiment), after which the scale was applied. And using statistical methods, through which the reality of sports and scouting activities at the Directorate of Sports and Scout Activity was identified from the point of view of teachers and supervisors of physical education in AlQadisiyah Governorate, and the researchers concluded the efficiency of the scale to measure the purpose for which it was prepared